(15x³-4x²) : (-5x)= [Obs: conta tambem pfv]
Soluções para a tarefa
Respondido por
1
Temos a seguinte expressão:
(15x³ + 4x²) / (-5x)
Vamos colocar o x em evidência e simplificar
(15x³ + 4x²) / (-5x) =
(x(15x² + 4x)) / x(-5) =
(15x² + 4x) / (-5) =
-15x²/5 - 4x/5 =
-3x² - 4x/5
(15x³ + 4x²) / (-5x)
Vamos colocar o x em evidência e simplificar
(15x³ + 4x²) / (-5x) =
(x(15x² + 4x)) / x(-5) =
(15x² + 4x) / (-5) =
-15x²/5 - 4x/5 =
-3x² - 4x/5
Perguntas interessantes
História,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Física,
1 ano atrás
Física,
1 ano atrás
Filosofia,
1 ano atrás
Português,
1 ano atrás